Ballistic Impact Behaviour of a Tempered Bainitic Steel Against 7.62 mm Armour Piercing Projectile - (:unkn) unknown (DEFENCE SCIENTIFIC INFORMATION DOCUMENTATION CENTRE, 2011)
In this study, occurence of failure after the interaction between an armour piercing 7.62 mm caliber projectile and a tempered bainitic steel has been investigated. The shot was performed at zero degree with a projectile velocity of 840 m/s. After the shot, microstructural and fractographical examinations were carried out on the sample taken from the perforated region. In the etched sample, it was observed that the morphology of the original microstructure had changed and adiabatic shear bands (ASBs) were formed in regions close to the direction of penetration. Main failure is ductile (plastic) deformation was followed by cleavage after shot. Cracks due to adiabatic shear band and formation of abrasive wear were seen. The perforation mode of the steel was a typical petalling.
Keywords: Armour steels; microstructure; ballistic; perforation mode; impact behaviour; armour piercing projectile; tempered bainitic steel; SLIDING WEAR BEHAVIOR; HIGH-STRENGTH; COMPOSITE ARMOR; PERFORMANCE; MICROSTRUCTURE; PENETRATION; VELOCITY; HARDNESS; DESIGN; PLATE